IMMOBILISASI Fe3+ DAN Cr6+ PADA GEOPOLIMER BERBASIS ABU LAYANG-ABU SEKAM PADI - Persada, Mega Bunga; Kusumastuti, Ella; Mahatmanti, F.Widhi (Universitas Negeri Semarang, 2018)
Immobilization of Fe3+ and Cr6+ by using geopolymer based on fly ash (FA) and rice husk ash (RHA) and the effect on quality of geopolymer qualitatively have been investigated. Type C fly ash from Karang Kandri power plant in Cilacap and rice husk ash from burning briks in Klaten Central Java was used as the raw material. Rice husk ash was added from 0-7.5 g to produce geopolymer with optimum compressive strength, which composition used for geopolymer synthesis with addition of Fe3+ and Cr6+ metal ions. Fe3+ and Cr6+ metal ions were added into geopolymer paste at the level of 20-100 mmol. The result showed that the addition of 3 g rice husk ash produce geopolymer with optimum compressive strength to 35.43 MPa. The addition of 60 mmol of Fe3+ and Cr6+ metal ions improve the compressive strength to 37.22 MPa and 36.4 MPa. Further addition of metal ions reduce these value and the lowest compressive strength was observed on the additon of 100 mmol of Fe3+ and Cr6+ namely 20.36 MPa and 20.74 MPa. Leaching test was conducted by using AAS, leaching tests show that geopolymers can immobilize Fe3+ metal ions more effectively when compared to Cr6+ metal ions which is distributed throughout the geopolymer and is not chemically bound making it easier to leach out.